A system modeling approach for business intelligence system design in the Indonesian kite string industry - Hendry Anggraito; Rina Fitriana; Dadan Umar Daihani; Emelia Sari (Universitas Ahmad Dahlan, 2026)
Kite strings in Indonesia are crafted by local artisans who have learned from their predecessors, but the industry struggles to deliver quality products that meet customer standards. A Systematic approach to this problem could involve designing a business intelligence (BI) system to improve decision-making. Based on the main premises of the kite string industry, this paper focuses on developing a causal loop diagram (CLD) model as a first step toward designing an effective BI system for the kite string industry. The CLD model captures the relationships between core variables and brain areas, offering crucial insights into customer perceptions, production quality, and market dynamics. Based on data up to October 2023, the study uses a systematic approach to pinpoint the feedback loops enabling product quality and business performance. This framework can be used as a strategic approach to assist in decision-making, refine operational processes, and enhance overall product quality. This research provides a new perspective to the literature by combining systems thinking into BI system design under the context of traditional industries as an elaboration of findings aimed to gain a competitive advantage in Indonesian kite string business practices.